Estetika dan Religi Penggunaan Rerajahan pada Masyarakat Bali - I Made Gami Sandi Untara; I Wayan Titra Gunawijaya (Jnanasidanta, 2020)
Rerajahan is Balinese Hindu culture as a local product of the genus of Balinese Hindus. Hindus in Bali firmly believe that this rerajahan contains magic. The magical powers that can be generated by the rerajahan are used for sacred purposes, namely for things related to Hinduism which are called "Panca Yadnya". in addition, rerajahan is also a very inspirational work of traditional art, and has become a source of ideas for some Balinese artists in creating individual works. The very expressive form of rerajahan with a variety of motifs which are stylized from natural and fictional forms, is a work of art that is attractive and has high aesthetic value, integrated with spiritual values. Balinese people consider rerajahan as a religious, magical and mystical art object. In rerajahan, between religious values and aesthetic values are present as one unit. Therefore, it is fitting that rerajahan be called one of the single manifestations of art with religion. This research uses a qualitative approach, in which the data in this study are collected through literature studies related to the essence of Rerajahan, collecting libraries including books related to Rerajahan. The data that has been collected is then reduced to determine the appropriate data for analysis using the hermeneutic method